Methods of CO₂ acquisition and costs reduction in shale rocks fracturing technology - Miedzińska, Danuta; Niezgoda, Tadeusz (My University, 2016)
The innovative method of shale gas recovery with the use of subcritical $CO_{2}$ is currently developed within the project titled »Development of guidelines for design of innovative technology of shale gas recovery with the use of liquid $CO_{2}$ on the base of numerical and experimental research – DIOX4SHELL«, supported by the National Centre for Research and Development (NCBR). The project is carried out by Polish company PGNiG and by academics from WAT, AGH and PW (Military University of Technology, AGH University of Science and Technology, and Warsaw University of Technology). Finding the best business model, in which costs of $CO_{2}$ production or acquisition are negligible is one of the most important factors influencing the economical effectiveness of the technology. The main part of known $CO_{2}$ acquisition methods is based on fuel purchase and its combustion, what is very expensive process. It results with the high $CO_{2}$ price, when purchasing from producer, about 300 zl/ton. This price is quite high, considering current low prices of natural gas. In the paper basic aspects of $CO_{2}$ acquisition from $CO_{2}$ producers, exhaust gases treatment plants or plasma gasification methods will be presented.
AGH Drilling, Oil, Gas
Keywords: fracturing; shale gas; carbon dioxide; economics